2020
DOI: 10.1101/2020.11.10.377333
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization and structural basis of a lethal mouse-adapted SARS-CoV-2

Abstract: The ongoing SARS-CoV-2 pandemic has brought an urgent need for animal models to study the pathogenicity of the virus. Herein, we generated and characterized a novel mouse-adapted SARS-CoV-2 strain named MASCp36 that causes acute respiratory symptoms and mortality in standard laboratory mice. Particularly, this model exhibits age and gender related skewed distribution of mortality akin to severe COVID-19, and the 50% lethal dose (LD50) of MASCp36 was ~100 PFU in aged, male BALB/c mice. Deep sequencing identifie… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
69
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(84 citation statements)
references
References 73 publications
14
69
0
1
Order By: Relevance
“…However, other changes among the constellations defining the VOC lineages might also play a role in the resulting in vivo phenotype. Indeed, the mouse-adapted variants reported by Gu et al 10 and later Sun et al 19 induced pathological and inflammation features that were not observed here, and were also associated with genetic changes outside of the spike. Further studies are needed to dissect the combinatory role of the mutations defining the SARS-CoV-2 VOCs.…”
Section: The B1351 and P1 Variants Efficiently Replicate In Mice Airwayssupporting
confidence: 48%
“…However, other changes among the constellations defining the VOC lineages might also play a role in the resulting in vivo phenotype. Indeed, the mouse-adapted variants reported by Gu et al 10 and later Sun et al 19 induced pathological and inflammation features that were not observed here, and were also associated with genetic changes outside of the spike. Further studies are needed to dissect the combinatory role of the mutations defining the SARS-CoV-2 VOCs.…”
Section: The B1351 and P1 Variants Efficiently Replicate In Mice Airwayssupporting
confidence: 48%
“…4, the three variants UK501Y.V1, SA501Y.V2, and BR501Y.V3 gained substantial ability to infect HeLa mouse-ACE2, which correlated with those pseudoviruses bearing single (K417N, K417T, E484K, and N501Y) and triple (K417N-E484K-N501Y) mutations. This agrees well with the recent reports where either single N501Y or triple K417N-Q493H-N501Y mutations were found in the mouse-adapted SARS-CoV-2 strains, although the triple mutant causes more severe acute respiratory symptoms and mortality in standard laboratory mice ( 50, 51 ). Single N501Y mutation found in UK501Y.V1 and two of three (K417N and N501Y) found in SA501Y.V2 and BR501Y.V3 therefore likely enhanced the binding to mouse ACE2 thereby improved entry efficiency into HeLa mouse-ACE2.…”
Section: Resultssupporting
confidence: 93%
“…S4). This finding indicates that N501Y plays a role in enhanced binding, which is consistent with earlier reports on both human and mouse ACE2 ( 39, 40, 50, 51 ). The single K417N mutation, however, decreased ACE2 binding by about 6.4-fold.…”
Section: Resultssupporting
confidence: 93%
“…The N501Y mutation in the RBD is predicted to generate new interactions between Y501 with mACE2-H353, and new polar interactions between Y501 and hACE2-K353 (Figure 1F). Our modeling supports the observation that viruses with K417N and N501Y mutations have increased affinity for mACE2, with both appearing in mouse-adapted SARS-CoV-2 (41).…”
Section: Resultssupporting
confidence: 86%